2003
DOI: 10.1046/j.1365-2400.2003.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality associated with catch and release of striped bass in the Hudson River

Abstract: Catch‐and‐release fishing has increased in many fisheries, but its contribution to fishing mortality is rarely estimated. This study estimated catch and release mortality rates of striped bass, Morone saxatilis (Walbaum), for the spring recreational fishery in the Hudson River. Treatment fish (caught with live bait on spinning gear) and control fish (captured by electric fishing) were placed in in situ holding pens for 5 days. Mortality rates were estimated using conditional instantaneous mortality rates and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 16 publications
5
18
0
Order By: Relevance
“…Injury data were aggregated into two categories (injured or not injured), and hooking location was aggregated into three categories for analysis (shallow, lip and mouth; deep, throat and gut; other, eye and foul hooked). The grouping of hooking location is consistent with other studies which have shown a correlation between mortality and deep hooking in the gills, oesophagus or throat (Muoneke and Childress, 1994;Diggles and Ernst, 1997;Millard et al, 2003). Fish were unhooked using pliers or de-hookers, then tagged with unique identifiable dart tag and released.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Injury data were aggregated into two categories (injured or not injured), and hooking location was aggregated into three categories for analysis (shallow, lip and mouth; deep, throat and gut; other, eye and foul hooked). The grouping of hooking location is consistent with other studies which have shown a correlation between mortality and deep hooking in the gills, oesophagus or throat (Muoneke and Childress, 1994;Diggles and Ernst, 1997;Millard et al, 2003). Fish were unhooked using pliers or de-hookers, then tagged with unique identifiable dart tag and released.…”
Section: Methodssupporting
confidence: 87%
“…Diggles and Ernst (1997) concluded that hooking location was the most important factor affecting mortality of two small reef fish species, wire netting cod (Epinephelus quoyanus) and yellow stripey (Lutjanus carponotatus) caught from the GBR. Hook location has also been a significant factor affecting survival of striped bass (Morone saxatilis) and chinook salmon (Oncorhynchus tshawytscha), with deep-hooked fish more likely to die than lip-hooked fish (Grover et al, 2002;Millard et al, 2003). The rates of deep hooking observed in our study varied between fish species, hook patterns and hook sizes.…”
Section: Hooking Locationmentioning
confidence: 51%
“…Ayvazian et al, 2002;Millard et al, 2003;Broadhurst et al, 2005;Butcher et al, 2006;Götz et al, 2007;Grixti et al, 2007;Alós et al, 2008a), and is considered the most important factor affecting PRM (Muoneke and Childress, 1994;Bartholomew and Bohnsack, 2005,). This was confirmed by our results, as AHL was the only significant predictor of mortality for S. aurata.…”
Section: Parameterssupporting
confidence: 87%
“…The experiments in the Negro River basin showed that all peacock bass mortalities were associated with gill and throat injuries, supporting the argument that hook location is a strong factor in fish mortality (Millard et al 2003;Alós 2009;Broadhurst et al 2012 a, b). Both fish which suffered throat injuries in our study died, while gill injuries resulted in death 40% of the time.…”
Section: Discussionmentioning
confidence: 59%